Factors affecting worker well-being the impact of change in the labor market - Polachek, S. W.; Tatsiramos, Konstantinos (Research in labor economics, 2014)
This volume contains new important research on worker well-being. Topics include employment contracts, compensation schemes, worker productivity, retirement decisions, the demographic transition, time allocation, and child labor. Among the questions answered are: How important is incentive pay in increasing worker productivity? Does monitoring productivity affect a worker's earnings trajectory? How is the decision to retire different in two-earner families compared to one-earner families? How did the evolution of the family affect men's and women's proclivities to work? Do welfare subsidies encourage recipients to spend additional productive time with their children? Can property titles (land reform) affect child labor in less developed country settings?